Respuesta:
[tex] {6}^{2} + {6}^{2} = {d}^{2} \\ { d }^{2} = 72 \\ d = \sqrt{72} \\ d = 6 \sqrt{2} [/tex]
[tex] {3}^{2} + {h}^{2} = {6}^{2} \\ {h}^{2} = 36 - 9 \\ h = \sqrt{25} \\ h = 5[/tex]
[tex] {2}^{2} + {3}^{2} = {l}^{2} \\ {l}^{2} = 4 + 9 \\ l = \sqrt{13} [/tex]
[tex] { (\frac{5}{2} )}^{2} + {ap}^{2} = {5}^{2} \\ {ap}^{2} = 25 - \frac{25}{4} \\ {ap}^{2} = \frac{75}{4} \\ ap = \sqrt{ \frac{75}{4} } \\ \frac{5 \sqrt{3} }{2} [/tex]
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Verified answer
Respuesta:
[tex] {6}^{2} + {6}^{2} = {d}^{2} \\ { d }^{2} = 72 \\ d = \sqrt{72} \\ d = 6 \sqrt{2} [/tex]
[tex] {3}^{2} + {h}^{2} = {6}^{2} \\ {h}^{2} = 36 - 9 \\ h = \sqrt{25} \\ h = 5[/tex]
[tex] {2}^{2} + {3}^{2} = {l}^{2} \\ {l}^{2} = 4 + 9 \\ l = \sqrt{13} [/tex]
[tex] { (\frac{5}{2} )}^{2} + {ap}^{2} = {5}^{2} \\ {ap}^{2} = 25 - \frac{25}{4} \\ {ap}^{2} = \frac{75}{4} \\ ap = \sqrt{ \frac{75}{4} } \\ \frac{5 \sqrt{3} }{2} [/tex]